Sialendoscopy for sialodocholithiasis following submandibular gland excision: six variations on a theme - Jennifer E. Douglas (KeAi Communications Co., Ltd., 2021)
Sialendoscopy is a minimally invasive technique that facilitates the diagnosis and treatment of sialolithiasis. This case series presents the novel use of sialendoscopy to treat sialodocholithiasis in six patients with a non-functional or surgically absent submandibular gland by a single surgeon at the University of Pennsylvania Health System between March 2013 and December 2019. The four female and two male patients had a median age of 56 years and mean follow-up of 16.2 months (range 1–44.5). All stones were successfully removed using sialendoscopy, and in 5 patients a combined approach was utilized. All patients remain asymptomatic at last clinical follow-up. We conclude that sialendoscopy is a viable, minimally invasive method for managing sialodocholithiasis in patients with prior submandibular gland excision or atretic gland. It is also useful as an assistive tool when approaching complex transcervical or transoral procedures in previously instrumented patients.